Особливості мовної ситуації у Східній Україні - Дроздова, І. П.; Чадаєва, К. Ю.; Грень, Лариса Миколаївна (Київський національний університет ім. Тараса Шевченка, 2019)
Стаття присвячена дослідженню мовної ситуації на Сході України, що пояснюється історичними та культурними аспектами, які мали місце, починаючи з ХVII століття до І чверті ХХІ століття; простежуються явища білінгвізму і полілінгвізму в окремих регіонах України; особлива увага приділена мовній ситуації, що склалася на тимчасово окупованих територіях на Сході України, де здійснюється тотальна політико-ідеологічна "русифікація"; доведено, що покращення мовної ситуації можливо за умов свідомого ставлення громадян України до збереження української літературної мови на всіх рівнях комунікації.

The article is devoted to the study of the linguistic situation in Eastern Ukraine, which is explained by the historical and cultural aspects that took place from the seventeenth century to the first quarter of the twenty-first century; tracing the phenomena of bilingualism and polilingualism in some regions of Ukraine; special attention is paid to the linguistic situation in the temporarily occupied territories in the Eastern Ukraine, where total political and ideological "Russification" is carried out; it is proved that the improvement of the language situation is possible under the conditions of conscious attitude of the citizens of Ukraine to preserving the Ukrainian literary language at all levels of communication.
Peculiarities of the language situation in Eastern Ukraine
Keywords: українська літературна мова; явища білінгвізму; політика; державний статус; "русифікація"; культура; language situation; Ukrainian literary language; state status; bilingualism phenomena; Eastern Ukraine